“RISK COMMUNICATION" EDUCATION AS AN EFFORT FOR CONTROL AND PREVENTION OF COVID-19 WITH THE TARGET OF ACADEMIC CITIZENS - Rana Nadiyah Adwinda; Santi Martini; Kurnia Dwi Artanti; Arief Hargono (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2023)
Introduction: Knowledge about COVID-19 in the community which is a new disease (emerging disease) is varied thus, the community must be given education so they can stop the transmission of COVID-19 infection. The activity in the form of education (risk communication) regarding COVID-19 aims as an effort to control and prevent COVID-19 with the target of the academic community. Methods: The form of activity is in the form of online seminars or webinars via the zoom platform which are carried out every week to two weeks with the target of the Universitas Airlangga academic community including students, educational staff, and lecturers. Education about COVID-19 must be carried out for the academic community considering the enormous potential of Airlangga University academics who live in Surabaya and areas in East Java with the hope that the Airlangga University academic community can become agents of change in their environment. Results: The provision of education is carried out in the form of virtual discussions which are packaged in the form of the "Casual Talk to Get to Know COVID-19 Closer" event which has been held since May 2020 with speakers from the academic community with the target audience of the academic community. Conclusion: Educational activities or risk communication that have been carried out to provide knowledge about COVID-19 so that the academic community is expected to contribute to breaking the chain of transmission of COVID-19 by implementing health and prevention behaviors.